Avaliação das interações entre a albumina sérica humana (ASH), complexos terpiridina de Rutênio(II) doadores de óxido nítrico (NO) e seus respectivos aqua complexos - Bessas, Naiara Cristina (2022)
Nitric oxide (NO) acts in different physiological processes, from antimicrobial and antiparasitic activities, control of coagulation and blood pressure, to neurotransmission and antitumor action. Among the exogenous NO donors, ruthenium nitrosyl/nitro complexes are potential candidates for prodrugs, due to their physicochemical properties, such as thermal stability and physiological pH (pH = 7.4). In addition, the release of NO by the aforementioned complexes can be controlled through chemical, electrochemical or even photochemical stimuli. In view of the above, terpyridine complexes of ruthenium(II) nitric oxide (NO) donors were synthesized and characterized, and the nitrosyl complexes of the type [Ru(bdq)(tpy)(NO)](PF6)3 and [Ru(bd)(tpy)(NO)](PF6)3, and the nitro complexes of the type [Ru(NO2)(bdq)(tpy)]PF6 and [Ru(NO2)(bd)(tpy)]PF6 – where tpy=2,2':6',2”-terpyridine; bdq=3,4-diaminobenzoic acid; and bd=o-phenylenediamine. In addition, the possible products of NO release were synthesized and characterized, these being the aqua terpyridine complexes of ruthenium(II) of the type Ru(H2O)(bdq)(tpy)](PF6)2 and Ru(H2O)(bd)(tpy)](PF6)2. The complexes [Ru(bd)(tpy)(NO)](PF6)3, [Ru(NO2)(bdq)(tpy)]PF6, [Ru(NO2)(bd)(tpy)]PF6, Ru(H2O)(bdq)(tpy)](PF6)2 and Ru(H2O)(bd)(tpy)](PF6)2 are unpublished complexes. In the meantime, it was proposed to evaluate the interactions between the terpyridine complexes of ruthenium(II) with the biomolecule responsible for the storage, diffusion, metabolism and excretion of endogenous or exogenous ligands, which is human serum albumin (HSA). The evaluation of interactions between HSA and the complexes [Ru(bdq)(tpy)(NO)](PF6)3, [Ru(bd)(tpy)(NO)](PF6)3, [Ru(NO2)(bdq)(tpy)]PF6, [Ru(NO2)(bd)(tpy)]PF6, Ru(H2O)(bdq)(tpy)](PF6)2 and Ru(H2O)(bd)(tpy)](PF6)2 via spectroscopy in the IR region showed that the complexes provide conformational changes in the secondary structure of HSA, more specifically in the α-helices of the protein, which is an indication that there was an interaction between the species in question. Subsequently, studies via fluorescence spectroscopy indicated that there is an interaction between the species, and the mechanisms of HSA fluorescence suppression in the presence of complex nitrosyls and complex nitros are dynamic, while for aqua complexes there is a contribution of both mechanisms, static and dynamic. The Ka values for the HSA–[Ru(bdq)(tpy)(NO)](PF6)3, HSA–[Ru(NO2)(bdq)(tpy)]PF6, HSA–[Ru(NO2)(bd)(tpy)]PF6 and HSA–Ru(H2O)(bdq)(tpy)](PF6)2 systems suggest that such interactions are stabilized with increasing temperature. However, for HSA–[Ru(bd)(tpy)(NO)](PF6)3 and HSA– Ru(H2O)(bd)(tpy)](PF6)2 systems, the results demonstrate that such interactions are destabilized with increasing temperature. The thermodynamic parameters for HSA–[Ru(bdq)(tpy)(NO)](PF6)3, HSA–[Ru(NO2)(bdq)(tpy)]PF6, HSA–[Ru(NO2)(bd)(tpy)]PF6 and HSA–Ru(H2O)(bdq)(tpy)](PF6)2 systems indicate that species interact via hydrophobic interactions. However, for HSA–[Ru(bd)(tpy)(NO)](PF6)3 and HSA–Ru(H2O)(bd)(tpy)](PF6)2 systems, the results suggest that the species interact via hydrogen bonds. The center-to-center distances between the Trp-214 residue and the complexes, estimated by the FRET theory, demonstrate that there is a transfer of energy by resonance from HSA to the complexes, resulting in the suppression of intrinsic fluorescence of HSA. The evaluation of the sites of interaction between HSA and the complexes via synchronous fluorescence suppression of the HSA indicates that the complexes [Ru(bdq)(tpy)(NO)](PF6)3, [Ru(NO2)(bdq)(tpy)]PF6 and Ru(H2O)(bdq)(tpy)](PF6)2 are found in a hydrophilic protein microenvironment, close to the Trp-241 residue, more exposed to the solvent, while the complexes [Ru(bd)(tpy)(NO)](PF6)3, [Ru(NO2)(bd)(tpy)]PF6 are located in a hydrophobic protein microenvironment, close to Tyr residues, less exposed to solvent. The evaluation of interactions between HSA and the aqua complexes, Ru(H2O)(bdq)(tpy)](PF6)2 and Ru(H2O)(bd)(tpy)](PF6)2, via differential pulse voltammetry (VPD) suggest that the alterations presented in the voltammetric profiles of the complexes in the presence of HSA are attributed to changes in their molecular environment, and such changes are characterized by the interaction between the species.